(untitled) (Journal of the College of Basic Education, 2022)
The research aims to ((contemplative thinking skills are included in the physics textbook of high school stage and the extent to which students have)), by answering the following questions: 1-What are the contemplative thinking skills that should be available in the physics textbook of the high school stage? 2-What is the physics textbook of high school stage content from the contemplative thinking skills? 3-What is the owning level of high school students for contemplative thinking skills? The researcher used the descriptive and analytical approach, and it was the research community is a physics textbook for fourth-grade science-based students, and all the teachers of physics who have an actual service of not less than ten years in the Rifai and Qalat Suker districts which are within the directorate of education of Dhi Qar, the total number of the research samples is (30), A random sample of them (25) were taken which were male and female teachers, in addition to the fourth-grade science students for the (2015-2016) academic year intentionally, from Qalat Suker high school for boy, they were (120) student. The researcher built and applied a list of the contemplative thinking skills and testing the contemplative thinking skills corresponding to the physics textbook after they have been presented and reviewed by experts, specialists, and proficient in the field of education, psychology, measurement, and teaching methods. All data was analyzed statistically using statistical methods by using Statistical Program for the Social Sciences (SPSS). The results showed the availability of a set of contemplative thinking skills illustrated in tables (3, 4, 5, 6, 7). Regarding the second question, the results showed that the third skill (access to conclusions) the first place with a relative weight of (76.81%), while the second skill (fallacies Detection) ranked occupies the fifth place with a relative weight of (45.73%). As regards to the third question, the results showed that the third skill (access to conclusions) occupies the first place with a relative weight of (63.22%), and the fifth skill (Develop proposed solutions) ranked fifth with a relative weight of (57.39%), and the total relative weight for (contemplative thinking skills test) was (60.49%), which is less than the assumption average (70%), which was reliable from the literature and the previous studies by the value of (9.51). According to the recent research results, the researcher concluded number of conclusions included : - The fourth grade science-based’ physics textbook has a limited possibility to prepare a student who is capable to owning a contemplative thinking skills. Related to these findings and conclusions, the researcher recommended for : - Review and rebuild the scientific fourth grade’ physics textbook depending on and according to the contemplative thinking skills. The researcher suggested some future researches and studies including : - Conduct similar researches in the various scientific fields which fit with the different thinking skills.